(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied about leakage radiation images obtained for two different dielectric-loaded surface plasmon polariton waveguides based on routing structures; linear couplers and bent waveguides. By simultaneously imaging the conjugated aperture and field planes of the microscope, we unambiguously quantify the degeneracy lift occurring for strongly interacting dielectric loaded surface plasmon polariton waveguides and visualize the symmetry of the coupled modes. We have obtained the wave vector distribution and showed its evolution with the bend radius. We have developed a numerical and an analytical analysis for momentum distribution. We have found that for large radii i.e. for vanishing bending loss, we can link the plasmon in Fourier space with the geometrical and modal properties of the bend structure. It was also found that the radial dependence of the wave vector distribution is governed by the phase difference. The obtained results were found in good agreement with previously obtained results.